The Influence Of Leadership, Work Environment And Motivation And Employee Career Development On Work Achievement In PT. Medisafe Technologies - Maverin; Kelvin; Juliana Mega; Ester Rawina; Hendry (Institute of Computer Science (IOCS), 2021)
This study aims to determine the effect of leadership, work environment, and employee career development on work achievement at PT. Medisafe Technologies Medan. This type of research is explanatory research. The population in this study were all employees who worked at PT. Medisafe Technologies as many as 211 employees. Due to the large number of population, the sampling technique will be reduced by using the Slovin formula with an error tolerance level of 5% so that there are 138 respondents. In the study which will be distributed with questionnaires measured by a Likert scale. The data analysis used multiple linear regression analysis and the coefficient of determination as well as simultaneous test and partial test. The results showed that leadership, work environment, and employee career development partially or simultaneously have a positive and significant effect on work achievement at PT. Medisafe Technologies Medan. Based on the results of this study, the implications for management are to further improve leadership, improve a better work environment, update the employee career development.